Gay Fatherhood in the NICU: Supporting the "Gayby" Boom. (August 2020) - Logan, Rickey
Abstract : Background: With advances in reproductive health, gay males are increasingly given the opportunity to reproduce. It is not a common occurrence for infants of gay male fathers to enter the neonatal intensive care unit (NICU); however, this may change and should be acknowledged. Purpose: To give insight into the barriers, perspectives, and stresses of gay male caregivers (families) in their time spent in the NICU and to offer recommendations as to how better to serve them and their families. Methods/Search Strategy: Searched using PubMed, CINAHL, SCOPUS, and Google Scholar. Key words used were "gay families, " "fatherhood, " "neonatal intensive care unit, " "lesbians, " and "surrogacy." Findings/Results: There remains a very limited amount of data for healthcare providers as these relate to gay male fathers in the NICU, aside from narratives. Most of the research and literature that highlight potential barriers stem from heterosexual fatherhood in the NICU and lesbian parenting in the healthcare system. Implications for Practice: To have an understanding and knowledge to improve support for gay fathers in the NICU. Implications for Research: Research on gay fathers in the NICU and further research on lower economic gay fatherhood and gay men of color and fatherhood are required. Because of the small sample size, multicentered studies may warranted to aid in clinical significance.